Sulphur nutrition management in Sub-Saharan Africa crop production: a systematic review - Moshi, Martin M.; Amuri, Nyambilila A.; Weil, Ray R. (Frontiers in Agronomy, 2025)
Sulphur (S) deficiency in Sub-Saharan Africa (SSA), driven by soil degradation and S-free fertilisers, threatens crop yield and protein quality. This systematic review synthesises four decades of studies (1980–2024) to assess soil S status, analysis methods, management challenges, and recommended rates for effective fertilisation to improve sustainable productivity. A systematic literature review was conducted following the preferred reporting items for systematic reviews and meta-analyses (PRISMA) framework to synthesise available evidence on S nutrient management in agricultural soils across SSA. The review revealed that S concentrations were generally higher in surface horizons compared to sub-surface layers, with vertical distribution influenced by soil texture, pedogenic processes, organic matter content, and fertiliser inputs. In highly weathered soils, S depletion was pronounced, contributing to widespread deficiencies across SSA’s agricultural landscapes. Analysis of S fertilisation practices showed a research cereal crop (s) emphasis, accounting for 65% of studies, followed by legumes with 25% and oilseeds with 10%. Most of the cereal studies have reported S application rates between 0 and 30 kg S/ha, with 71% of studies applying ≤20 kg S/ha. Legumes, by contrast, received higher rates (21–40 kg S/ha), typically through potassium sulphate or nitrogen-phosphorus-sulphur (NPS) blended fertilisers. Yield responses to S application varied significantly by crop type. Maize exhibited the higher yield increase, ranging from 20% to 260% depending on the fertiliser application rate, followed by wheat and rice. Legumes such as soybeans showed more modest increase of 25%, while oilseeds like canola and sesame responded minimally, even under higher S inputs. These findings underscore the need for crop- and site-specific S management strategies in SSA. The adoption of soil testing and decision-making frameworks such as the 4R nutrient stewardship (right source, rate, time, and place) is recommended to optimise crop yield and reduce environmental risks associated with nutrient mismanagement.